Evaluation of serum Podocalyxin in Iraqi women with Polycystic Ovary Syndrome - Fadhil, Noor Mohammed; hamdi, Rana ali (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Polycystic ovarian syndrome is the most common endocrine disease in females of childbearing time of life. Women with polycystic ovarian syndrome  have a higher chance of developing complications such as dyslipidemia, hypertension, and obesity. Obesity is a state of extreme fat buildup which leads to the development of multiple complications involving non-alcoholic fatty liver disease, cardiovascular disease and type2 diabetes mellitus. Podocalyxin is an element of the endothelial cells plasma membranes that is widely spread, it is limited to the luminal membrane area and is irregularly located on the surface of endothelial cells lining blood vessels.Objectives: To estimate serum Podocalyxin in polycystic ovarian syndrome women and compare its level with healthy controls. Also, to find the correlation between serum Podocalyxin and anthropometrics parameters which are (body mass index, waist circumference, waist to hip ratio). Methods: This case control study included 124 women who were grouped into 2 groups: group 1 included 63 females diagnosed with PCOS (patients) and group 2 included 61 healthy women (controls). Serum podocalyxin was measured by Enzyme-linked immunosorbent assay technique and anthropometrics measures (“body mass index (BMI), waist circumference (WC) and waist to hip ratio WHR”) were done.Results: The results of this study showed significantly high mean BMI(P=0.001), WC(P=0.002) and WHR(P=0.001) in patients as compared to healthy controls. The results also showed a significant increase in mean value of serum PODXL (P=0.001) in PCOS females when compared with healthy controls. In patients group, significant positive correlations were found between serum PODXL and BMI (r=0.395, p=0.001), waist circumference (WC) (r.=0.433, p.=0.001) and waist to hip ratio (WHR) (r.=0.427, p.=0.001 ).Conclusion: PCOS women have greater body mass represented by BMI, WC and WHR which reflect the risk of multiple complications like hypertension, dyslipidemia and cardiovascular disease. Moreover, PCOS women have higher serum PODXL which is considered as a marker for the vasculature thus might be a potential marker for prediction of early atherosclerosis.